The Labour Party and the Nursing Profession - MacDonald, James Ramsay, 1866-1937 (London : The Labour Party (London : Co-operative Print. Society Ltd.), 1927)
1927 1927 1920s 40 pages 14 one week-end a fortnight and one reporting a week-end monthly for all grades. Two reported a week-end monthly for sisters, whereas the nurses and probationers received only one day monthly. The rest have usually one day off a month, getting away the previous evening. The Poor Law infirmaries usually allow hours off duty per day and one day off per week. The long week-end is quite exceptional, only one Poor Law infirmary reporting a week-end every six weeks. Sisters sometimes get an extra day off once a month. Arrangements in special hospitals seem to be almost as good as those for the London general hospitals, most of them giving sisters one weekend per month, and the nurses and probationers one day per month with a sleeping-out pass the night before. In fever hospitals the usual off-duty hours are three hours daily, half a day weekly and one day monthly. Only one hospital arranged for a full week-end. In cottage hospitals the usual off-duty hours are two hours daily, half a day weekly and one day monthly. HOLIDAYS. The usual holidays are four weeks for sisters and three weeks for nurses and probationers. The large general hospitals sometimes give sisters five or even six weeks —four weeks in summer plus a week or two in spring. Some nurses and probationers receive only two weeks. In one hospital sisters receive only two weeks. MEALS. The usual custom in all kinds of hospitals is to allow one half-hour off for each meal. Sometimes 45 minutes are allowed for dinner. One London hospital reported that 45 minutes are allowed for all meals. Three Poor Law infirmaries and one hospital allow one full hour for dinner. Nurses on night duty always have breakfast before going on duty, dinner when coming off duty, and a light luncheon at 11-30 a.m. served in the nurses' dining room. In the majority of cases the midnight meal and tea at 4-30 a.m. are prepared by the nurses themselves in the ward kitchens. Eleven hospitals reported that the midnight meal is served hot in the nurses' home. In this case the nurses leave the wards in three groups. One hospital reported that both the midnight meal and tea at 4 a.m. were served in the nurses' dining room. One hospital allows two hours for the midnight meal. LIVING ACCOMMODATION. In the vast majority of cases nurses sleep in the nurses' home, a separate building away from the hospital. One nurses' home has 160 separate bedrooms, a sitting-room, a recreation room, a library, class room, and 36 bathrooms. Seven hospitals specifically stated that all nurses have separate bedrooms. One reported that all senior nurses and probationers have single rooms, but that some of the junior nurses share rooms, none with more than two nurses in them. One hospital reported that sisters have bed-sitting rooms or two rooms and a sisters' dining room, while the nurses and probationers have their own dining-room, a sitting-room, and separate bedrooms. In fourteen of the large general hospitals the nurses sleep in hospital, usually on the first or second floor, while the patients are on the ground floor, or else in the administrative block of the institution. Two such hospitals have a separate villa on the grounds for nurses on night duty. There is rarely a nurses' home for the small hospitals. In one Poor Law infirmary the cubicles ware only "curtained." 126/TG/RES/X/1036A/14